Block copolymer containing polar segments, preparation method thereof, and application thereof
By using block copolymers containing polar segments as processing additives in thermoplastic resin processing, the 'shark skin' phenomenon on the extrudate surface and melt rupture problems are solved, and the effect of improving processing performance and economic benefits is achieved, and it is in line with environmental protection requirements.
Patent Information
- Application Number
- CN202411773520.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-05
AI Technical Summary
In thermoplastic resin processing, the surface of the extrudate is prone to 'shark skin', and the melt breaks seriously, affecting product quality and production efficiency.
Block copolymers containing polar segments are used as processing aids. Through specific structures and preparation methods, the intermolecular force is improved, the die accumulation is reduced, the melt is cracked, and the torque extrusion pressure is reduced.
It effectively reduces the oral mold accumulation material during resin processing, eliminates the phenomenon of 'shark skin', improves processing performance and economic benefits, and does not contain fluorine and silicon, and is suitable for environmental protection and high safety fields.
Smart Images

Figure CN119264409B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material processing, and in particular to a block copolymer containing a polar segment, a preparation method thereof, and an application thereof. Background Art
[0002] In order to achieve the goals of increasing production and reducing consumption, saving energy and reducing emissions, the plastics industry needs to continuously improve processing technology, and at the same time, it needs to apply efficient processing aids to improve economic benefits. In the polymer processing industry, large-scale film blowing, wire drawing, injection molding, and extrusion equipment all require continuous production, reduce energy consumption, and extend the time for cleaning equipment and changing screens. In order to improve production efficiency and reduce production costs, the method of increasing the screw speed of the extruder to speed up the extrusion speed is usually adopted. However, when the extrusion speed exceeds a certain limit, the surface quality of the extrudate will deteriorate, and the "shark skin" phenomenon will appear. The extrudate will be spiral or bamboo-shaped, resulting in unstable flow. The subsequent material surface of the extrudate usually cannot flow fast enough to keep up with the main body of the extrudate, and ruptures occur in the melt, resulting in serious loss of surface performance of the extrudate. Therefore, it is necessary to use processing aids in actual production to help manufacturers solve the above problems.
[0003] In the development history of polymer processing aids, the earliest processing aids used were polyethylene wax, stearate and fatty acid derivatives, etc.; however, they are all low molecular weight substances with poor thermal stability, which can easily cause material deposition in the mold. The most common substances on the market today are polymer processing aids (PPA), mainly fluorinated polymer additives, silicone additives, dendrimers, and polyethylene glycol. First of all, fluororubber additives belong to fluoropolymer additives. Fluororubber additives refer to a type of compound containing fluoroolefin copolymers used to improve the processing performance of resins and improve product quality. Since fluorinated polymers will produce fluorinated toxic gases such as ammonium perfluorooctanoate (PFOA) at high temperatures. Therefore, the research and development direction of processing aids is also turning to fluorine-free PPA substitutes. This means that the research and development of fluororubber additives will face new challenges, but will also bring more benefits to human and environmental health. Secondly, in the category of silicone processing aids, Dow Corning's polydimethylsiloxane processing aid is the most famous product in this field. Although silicone processing aids play an important role in plastic processing, their use also has some potential problems. For example, silicone polymer chains are flexible, have good thermal stability and low surface energy, but during plastic processing, due to the low surface energy of silicone, it is easy to migrate to the surface of the screw, causing slippage, which in turn affects production efficiency. At the same time, organosiloxane decomposes at high temperatures to generate short-chain oligomers, which are classified as substances of high concern by the European Chemicals Agency, so the development of silicone-free processing aids has also become a focus of industry attention.
[0004] In view of the above problems, the current solutions are mainly:
[0005] Patent document 1 (CN102648241A) discloses that alkyl methacrylate polymers are used as processing aids in polyolefin resins to improve processing performance. The polymerization method is mainly emulsion polymerization to obtain a powdery substance. The disadvantage is that the preparation process is complicated and the cost is high.
[0006] Patent document 2 (CN118019793A) discloses a method for preparing a fluorine-free blend as a polymer processing aid: any two of polyethylene glycol, sorbitol ester or metal salt of fatty acid are blended in proportion to obtain a new processing aid; however, the additives used in this patent are all low molecular weight substances with low thermal stability, and are prone to form black spots on the surface of the product or film, thereby affecting the product quality.
[0007] Patent document 3 (CN117693543A) discloses a polymer processing aid (PPA) containing a polyamide-polyether structure. The processing aid is based on a polyamide-polyether structure and can reduce melt fracture during the extrusion of polyolefin resins. However, the amide structure is not resistant to yellowing under long-term exposure to light and high temperature, which will cause the surface color of the processed product to change, affecting the appearance of the product.
[0008] Patent document 4 (CN105524448A) discloses a mixture of polar end-group polymer particles and micro-nano particles as a polymer processing aid, which can increase lubricity during 3D printing. However, most processing aids are suitable for commonly used 3D printing substrates such as polylactic acid, and the processing lubrication effect on polyolefin resins, which are used in the largest amount, is unknown.
[0009] Patent document 5 (CN101437890A) discloses a polymer processing aid composed of a surfactant and a lubricant, which can increase the volume during processing and improve processing performance. However, the mixture composed of the surfactant and the inorganic filler may cause crystal point problems during the film blowing process.
[0010] In addition, the hyperbranched polymers disclosed in Patent Document 6 (CN108559067A) and Patent Document 7 (CN101033279A) are used as processing aids in thermoplastic resins to improve resin processing fluidity, but their production costs are high and the process requirements are complex. Summary of the invention
[0011] Technical problems solved by the present invention:
[0012] It is used to solve the "shark skin" phenomenon that occurs on the surface of the extrudate in the existing thermoplastic resin processing, and to improve the melt fracture phenomenon that occurs during the extrusion process.
[0013] The technical solution adopted by the present invention is:
[0014] In view of the above technical problems, the object of the present invention is to provide a block copolymer containing polar segments, a preparation method thereof, and an application thereof. The block copolymer provided by the present invention is used as a molding processing aid for thermoplastic resins. The processing aid can effectively reduce the phenomenon of material accumulation at the die mouth; prevent the "shark skin" phenomenon caused by melt fracture; take effect quickly, reduce dead material in the barrel, significantly extend the cleaning screw cycle; reduce the torque extrusion pressure, and improve the processing performance of thermoplastic resins and the economic benefits of the factory.
[0015] Specifically,
[0016] First, the present invention provides a block copolymer containing polar segments, and the structural formula of the block copolymer is shown in Formula I:
[0017]
[0018] Formula I
[0019] n1≥1, n2≥1, n3≥2, n4≥1;
[0020] R1 is selected from any one of a hydrogen group, an alkoxy group having a carbon number of C1, C2 or C4, an isopropoxy group, a methyl group, an ethyl group, a tert-butyl group and a thiol group;
[0021] R2 is selected from any one of methylene, imino, carbonyl, -O- and -S-;
[0022] R3 is selected from any one of methyl, chloromethylene, methylenehydroxyl, and formula II;
[0023]
[0024] Formula II
[0025] n5 is selected from 0 or 1;
[0026] R4 is selected from any one of methylene and carbonyl;
[0027] R5 is selected from any one of a hydrogen group, a carboxyl group, a hydroxyl group, and a methyl group.
[0028] According to some preferred embodiments, in the above-mentioned block copolymer containing polar segments, at least one of the substituents R2 and R4 in the structure is a methylene group.
[0029] Second, the present invention provides a method for preparing the aforementioned block copolymer containing polar segments, comprising the following steps:
[0030] S1: placing a cyclic compound containing a heteroatom in a reaction system, heating it, and then dropping an initiator and a catalyst to obtain an intermediate 1 through reaction;
[0031] S2 Add fatty acid to the reaction system to obtain intermediate 2;
[0032] The low-boiling substances are removed from the intermediate S3 to obtain a block copolymer;
[0033] In the aforementioned S1, the cyclic compound containing heteroatoms includes at least one of ethylene oxide, propylene oxide, epichlorohydrin, glycidol, allyl alcohol glycidyl ether, ethoxyvinyl glycidyl ether, caprolactam, oxetane, ε-caprolactone, β-propiolactone, β-butyrolactone, 3-methyltetrahydrofuran, lactide, and thietane.
[0034] According to some preferred embodiments, in S1 and / or S2, the reaction temperature is 30-100° C., and the reaction time is 4-18 h.
[0035] According to some more preferred embodiments, in S1 and / or S2, the reaction temperature is 40-80° C., and the reaction time is 4-10 h.
[0036] According to some preferred embodiments, the molar ratio of the cyclic compound containing a heteroatom, the initiator, the catalyst, and the fatty acid is (1-5):(0.01-0.1):(0.01-0.3):(1-5).
[0037] According to some preferred embodiments, the initiator includes at least one of C1-C8 fatty alcohol (linear or branched), butanediol, isopropanol, and tert-butanol.
[0038] According to some preferred embodiments, the catalyst includes at least one of sodium hydroxide, potassium hydroxide, triethylamine and phosphazene base P4-t-Bu solution (1-tert-butyl-4,4,4-tris(dimethylamino)-2,2-bis[tris(dimethylamino)-phosphoranylideneamino]-2Λ5,4Λ5-bis(phosphorus nitrogen compound)).
[0039] According to some preferred embodiments, the fatty acid includes at least one of acetic acid, sebacic acid, butyric acid, caproic acid, caprylic acid, capric acid, stearic acid, lauric acid, and myristic acid.
[0040] Third, the present invention provides an application of the aforementioned block copolymer in a thermoplastic resin processing aid.
[0041] The beneficial effects achieved by the present invention are:
[0042] (1) The block copolymer provided by the present invention contains a large number of polar groups, which increase the intermolecular forces and form a droplet-shaped dispersed phase in the matrix resin. In the process of plastic processing, the fluidity of polyolefins is improved, the onset time is fast, the torque extrusion pressure is reduced, and the surface "shark skin" phenomenon is eliminated, which can effectively reduce the die accumulation during resin processing.
[0043] (2) The block copolymer provided by the present invention does not contain fluorine or silicon, and therefore does not release harmful substances during production and use. It is environmentally friendly and meets environmental protection requirements. This property makes it suitable for use in fields that require high safety, such as food packaging.
[0044] (3) The block copolymer provided by the present invention is suitable for injection molding and extrusion processes for coating pipes, profiles, and cables; it can also be used in the processing of films (blown films, stretched films, and cast films), reducing energy consumption, extending the time for cleaning equipment and changing screens, and improving the economic benefits of the factory.
[0045] (4) The preparation method provided by the present invention is simple to operate and has high feasibility. It only requires adding the cyclic compound and the fatty acid step by step and reacting them in the presence of a catalyst and an initiator to obtain the block polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1-8 is the extruded spline surface state diagram ( Figure 1 For blank sample, Figure 2 For processing aid 1, Figure 3 For processing aid 2, Figure 4 For processing aid 3, Figure 5 For processing aid 4, Figure 6 For processing aid 5, Figure 7 As processing aid 6, Figure 8 It is a processing aid 7); the magnification of the microscope is 4*0.1 (the magnification of the eyepiece and the objective lens of the magnifier is multiplied);
[0047] Figure 9-16 This is the actual picture of the die material accumulation ( Fig. 9 For blank sample, Fig.10 For processing aid 1, Fig.11 For processing aid 2, Fig.12 For processing aid 3, Fig.13 For processing aid 4, Fig.14 For processing aid 5, Fig.15 As processing aid 6, Fig.16 As a processing aid 7). DETAILED DESCRIPTION
[0048] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0049] Embodiment 1:
[0050] This embodiment provides a block copolymer processing aid containing polar segments, which is prepared by the following method: first, 40g of epichlorohydrin is added to a four-necked reaction bottle, and when the reaction temperature reaches 45°C, 2g of tert-butyl alcohol and 1g of sodium hydroxide are added, and the reaction is stirred for 4h; then 122.9g of stearic acid is added, and after stirring for 3h, the mixture is passed into a desulfurization device and heated to 140°C for desulfurization treatment for 10min. If there is still distillate left, the reaction is continued for 1h, and if no distillate is produced, the reaction is stopped. The temperature is subsequently reduced to room temperature to obtain a product, namely, a block copolymer processing aid 1, as shown in Formula 1 below.
[0051]
[0052] Formula 1
[0053] Embodiment 2:
[0054] The present embodiment provides a block copolymer processing aid containing polar segments, which is prepared by the following method: first, 40g of allyl alcohol glycidyl ether is added to a four-necked reaction bottle, and when the reaction temperature reaches 45°C, 2g of tert-butyl alcohol and 1g of sodium hydroxide are added, and the reaction is stirred for 4h; then 70.81g of lauric acid is added, and after stirring for 3h, the temperature is passed into a desulfurization device and heated to 140°C for desulfurization treatment for 10min. If there is still distillate left, the reaction is continued for 1h, and if no distillate is produced, the reaction is stopped. The temperature is subsequently reduced to room temperature to obtain a product, namely, a block copolymer processing aid 2, as shown in Formula 2 below.
[0055]
[0056] Formula 2
[0057] Embodiment 3:
[0058] This embodiment provides a block copolymer processing aid containing polar segments, which is prepared by the following method: first, 40g of caprolactam is added to a four-necked reaction bottle, and when the reaction temperature reaches 45°C, 2g of butanediol and 1g of sodium hydroxide are added, and the reaction is stirred for 4h; then 100.09g of stearic acid is added, and after stirring for 3h, the mixture is passed into a desulfurization device and heated to 140°C for desulfurization treatment for 10min. If there is still distillate left, the reaction is continued for 1h, and if no distillate is produced, the reaction is stopped. The temperature is subsequently reduced to room temperature to obtain a product, namely, block copolymer processing aid 3, as shown in Formula 3 below.
[0059]
[0060] Formula 3
[0061] Embodiment 4:
[0062] This embodiment provides a block copolymer processing aid containing polar segments, which is prepared by the following method: first, 50g of lactide is added to a four-necked reaction bottle, and when the reaction temperature reaches 45°C, 2g of ethanol and 1g of potassium hydroxide are added, and the reaction is stirred for 4h; then 40.27g of caproic acid is added, and after stirring for 3h, the mixture is passed into a desulfurization device and heated to 140°C for desulfurization treatment for 10min. If there is still distillate left, the reaction is continued for 1h, and if no distillate is produced, the reaction is stopped. The temperature is subsequently reduced to room temperature to obtain a product, namely, block copolymer processing aid 4, as shown in Formula 4 below.
[0063]
[0064] Formula 4
[0065] Embodiment 5:
[0066] This embodiment provides a block copolymer processing aid containing polar segments, which is prepared by the following method: first, 50g of ε-caprolactone is added to a four-necked reaction bottle, and when the reaction temperature reaches 80°C, 0.2g of phosphazene base P4-t-Bu solution is added, and 2g of methanol is added after stirring for 4h; then 88.58g of sebacic acid is added, and after stirring for 3h, the temperature is passed into a desulfurization device and heated to 140°C for desulfurization for 10min. If there is still distillate left, the reaction is continued for 1h, and if no distillate is produced, the reaction is stopped. The temperature is subsequently reduced to room temperature to obtain a product, namely, a block copolymer processing aid 5, as shown in Formula 5 below.
[0067]
[0068] Formula 5
[0069] Embodiment 6:
[0070] This embodiment provides a block copolymer processing aid containing polar segments, which is prepared by the following method: first, 40g of 3-methyltetrahydrofuran is added to a four-necked reaction bottle, and when the reaction temperature reaches 80°C, 2g of isopropanol and 1g of potassium hydroxide solution are added, and the reaction is stirred for 4h; then 106.05g of myristic acid is added, and after stirring for 3h, the mixture is passed into a desulfurization device and heated to 140°C for desulfurization treatment for 10min. If there is still distillate left, the reaction is continued for 1h, and if no distillate is produced, the reaction is stopped. The temperature is subsequently reduced to room temperature to obtain a product, namely, block copolymer processing aid 6, as shown in Formula 6 below.
[0071]
[0072] Formula 6
[0073] Embodiment 7:
[0074] This embodiment provides a block copolymer processing aid containing polar segments, which is prepared by the following method: first, 40g of thiobutane is added to a four-necked reaction bottle, and when the reaction temperature reaches 80°C, 2g of isopropanol and 0.3g of phosphazene base P4-t-Bu solution are added, and the reaction is stirred for 4h; then 153.48g of stearic acid is added, and after stirring for 3h, the temperature is passed into a desulfurization device and heated to 140°C for desulfurization treatment for 10min. If there is still distillate left, the reaction is continued for 1h, and if no distillate is produced, the reaction is stopped. The temperature is subsequently reduced to room temperature to obtain a product, namely, block copolymer processing aid 7, as shown in Formula 7 below.
[0075]
[0076] Formula 7
[0077] Test example
[0078] The processing aids 1-7 in the above examples 1-7 were respectively made into masterbatches with LLDPE using a twin-screw extruder. The content of the processing aids in the masterbatches was 5 wt%.
[0079] 1. Experimental materials and models are shown in Table 1.
[0080] Table 1
[0081]
[0082] 2. The experimental formula is shown in Table 2.
[0083] Table 2
[0084]
[0085] 1 wt% of the above masterbatches 1, 2, 3, 4, 5, 6, and 7 were added to LLDPE and mixed to obtain experimental samples for the following experiments.
[0086] The critical shear rate of melt fracture of the above experimental samples was tested by high pressure capillary rheometer. The extrusion experiment was carried out on a high pressure capillary rheometer (aspect ratio 20 / 2, temperature 180°C), and the surface melt fracture of the capillary rheometer extruded specimen was observed by optical microscope. Before switching each sample, it was cleaned with pure material, and then the same result of experimental sample 1 was repeated with pure material before continuing to the next sample.
[0087] Experimental operation process:
[0088] (1) Use about 20g of pure LLDPE to fill the tube cavity, press it to the second scale with a hand pressure rod, manually operate the hydraulic press to drive the fixed pressure rod to press down, keep warm for 3 minutes, and manually press it out after completion to observe whether the tube cavity is cleaned. Otherwise, repeat this operation;
[0089] (2) Take about 20g of the material to be tested and repeat the above operation to rinse the lumen so that the results are closer to the actual application situation;
[0090] (3) Carry out extrusion test on the material to be tested according to the operating procedures;
[0091] (4) Wash and lubricate the machine before testing the next material.
[0092] The experimental data are shown in Table 3, and the surface state diagram of the extruded spline is shown in Figure 1-8 shown.
[0093] Table 3
[0094]
[0095] From Table 3 and Figure 1-8 It can be seen from the results that the pure material without processing aids exhibits melt fracture at a shear rate of 1401 / s under the above experimental conditions. After adding different processing aids, the critical shear rate becomes higher, indicating that the processing aid provided by the present invention has a significant effect on improving the processing performance of the material.
[0096] The torque rheometer was used to extrude under the capillary die, and the critical time to eliminate melt fracture and the die material accumulation after 6 hours of extrusion were tested at a constant speed (120 rpm) and 1000 ppm of the above samples. Before switching samples each time, the samples were cleaned with pure material, and then the same results of experimental sample 1 were repeated with pure material before continuing to the next sample. The experimental formula is shown in Table 4.
[0097] Table 4
[0098]
[0099] Operation process: Set the extruder zone experimental temperature to 150℃, 180℃, 180℃, 180℃, and the extrusion speed to 120rpm. The experimental data obtained are shown in Table 5. The die accumulation is shown in Figure 9-16 shown.
[0100] Table 5
[0101]
[0102] From Table 5 and Figure 9-16 It can be seen from the results that the pure material without processing aids has melt fracture under the above experimental conditions of 120rpm and is not eliminated. After adding different processing aids, the critical time to eliminate melt fracture is shortened. Moreover, compared with the pure material, the die accumulation after 6h of long-term extrusion is greatly reduced by adding the processing aids of the present invention. This shows that the processing aids of the present invention have a significant effect on improving the processing performance of the material substrate.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a block copolymer containing polar segments, characterized in that: The steps include: S1: placing a cyclic compound containing a heteroatom in a reaction system, heating it, and then dropping an initiator and a catalyst to obtain an intermediate 1 through reaction; S2 Add fatty acid to the reaction system to obtain intermediate 2; The low-boiling substances are removed from the intermediate S3 to obtain a block copolymer; In the aforementioned S1, the cyclic compound containing heteroatoms includes at least one of ethylene oxide, propylene oxide, epichlorohydrin, glycidol, allyl alcohol glycidyl ether, ethoxyvinyl glycidyl ether, caprolactam, oxetane, ε-caprolactone, β-propiolactone, β-butyrolactone, 3-methyltetrahydrofuran, lactide, and thietane; The fatty acid includes at least one of stearic acid, lauric acid, and myristic acid; The molar ratio of the cyclic compound containing heteroatoms, the initiator, the catalyst and the fatty acid is (1-5):(0.01-0.1):(0.01-0.3):(1-5).
2. The method for preparing a block copolymer containing polar segments according to claim 1, characterized in that: In S1 and / or S2, the reaction temperature is 30-100°C, and the reaction time is 4-18h.
3. The method for preparing a block copolymer containing polar segments according to claim 2, characterized in that: In S1 and / or S2, the reaction temperature is 40-80°C and the reaction time is 4-10 hours.
4. The method for preparing a block copolymer according to any one of claims 1 to 3, characterized in that: The initiator includes C1-C8 fatty alcohol.
5. The method for preparing a block copolymer according to claim 4, characterized in that: The initiator includes at least one of butanediol, isopropanol and tert-butanol.
6. The method for preparing a block copolymer according to any one of claims 1 to 3, characterized in that: The catalyst includes at least one of sodium hydroxide, potassium hydroxide, triethylamine and phosphazene base P4-t-Bu solution.
7. Use of the block copolymer obtained by the preparation method according to any one of claims 1 to 6 as a thermoplastic resin processing aid.
Citation Information
Patent Citations
Ultra-branched polymer used as polythene processing auxiliary agent and synthetic method
CN101033279A
Compatibilized polymer processing additives
CN101437890A
Processing aid for polyolefin resins, polyolefin resin compositions, and molded products
CN102648241A
Application of polymer processing auxiliary agent in 3D printing
CN105524448A
Long-chain branching polymer-type processing aid and preparation method and application thereof
CN108559067A